Effects of boron modifications on phase nucleation and dissolution temperatures and mechanical properties in 9%Cr steels: sensitivity and stability. (19th February 2020) - Akhtar, Modassir; Khajuria, Akhil; Pandey, Manish Kumar; Ahmed, Iqbal
Abstract: Effects of boron modifications in 9%Cr steels were investigated by considering design parameters, i.e., sensitivity and stability with the help of analytical equations as reported previously. The interference of phase temperature(s) for a phase on the rest of the phases was discussed. Overlapping of phase temperature for two distinct phases was observed. Invariability, an invariable composition(s), and susceptibility for phase temperatures were determined. Full stability, partial stability, and no stability for phase/property were analytically discussed. In this respect, boron modification only delayed the formation of detrimental phases. A mixture of positive, negative, and transient sensitivity was observed for some phases. However, a few phases showed both negative and transient sensitivities. Nevertheless, only negative sensitivity and only positive sensitivity found in some phases and properties. At last, the self-changing capability of linear and non-linear functions was found to confirm the nature of boron (i.e., minimization or maximization or point of inflexion). A decrease in a phase/property band was observed for designed boundary condition (DBC) as regards studied boundary condition (SBC). For phases and properties, the band of variation decreased by ∼52% and ∼32%, respectively, for the DBC as regard SBC and verified upper limit of 350 ppm boron modification as optimized structure-property in 9%Cr steels.